Research progress of measuring tools for nursing students’ clinical learning environment - Xu, Yun; Wang, Qing; Wei, Qi (Frontiers in Medicine, 2025)
ObjectiveTo understand the current situation and progress of clinical learning environment measurement tools for nursing students, this paper reviews the relevant research on clinical learning environment measurement tools for nursing students.MethodsThree databases (Web of Science, PubMed, and CNKI) were searched for relevant articles. Research articles that met specific criteria were included, with identified articles initially screened by title and keyword. Then the abstracts were screened for relevance, and the full text was read for validation before inclusion. Descriptive analysis was performed with relevant findings from data retrieved from various sources.ResultsWe included 19 articles that met the criteria, and introduced nine measurement scales, which completed the reliability and validity test through empirical research, providing an important reference for the assessment of clinical learning environment for nursing students. The Clinical Learning Environment and Supervision instrument (CLESI) has been translated into many languages and is widely used.ConclusionThis review includes multiple clinical learning environment measurement tools for nursing students, which have important value in evaluating the clinical environment of nursing students and can provide reference for scholars to carry out relevant research and practice. It also introduces the research prospects in this field, aiming to inspire future research.